PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PT GUDANG GARAM TBK PERIODE 2012-2018 - Rio Baviga; Mauledy Ahmad (LPPM - STIE SAKTI ALAM KERINCI, 2020)
The study aims to determine: 1) The extent to which the influence of the Liquidity on Dividend Policy partially on PT Gudang Garam Tbk?, 2) The extent to which the influence of the Profitability on Dividend Policy partially on PT Gudang Garam Tbk?, 3) The extent tp which the influence of the Liquidity and Profitability on Dividend Policy simultaneously on PT Gudang Garam Tbk?, 4) How much influence Liquidity and Profitability on Dividend Policy on PT Gudang Garam Tbk?. The type of data used in this study is secondary data financial statements PT Gudang Garam Tbk. The data analysis tool used is multiple linear berganda. Based on the result of the study showed that : Partially Liquidity has no effect on Dividend Policy. Partially Profitability has no effect on Dividend Policy. Simultaneously liquidity and Profitability has no effect on Dividend Policy. The amount of influence exerted by the Liquidity and Profitability variables on Dividend Policy in PT Gudang Garam Tbk in 2012-2018 is 50% while the remaining 50% is influenced by other factors not examined in this study.